Meta analysis of ovulation induction effect and pregnancy outcome of acupuncture & moxibustion combined with clomiphene in patients with polycystic ovary syndrome - Yang, Lijie; Yang, Wanqiu; Sun, Minghan; Luo, Linjie; Li, Hong Ru; Miao, Runqing; Pang, Li; Chen, Yajie; Zou, Kun (Frontiers in Endocrinology, 2023)
Objective: Using Mesh Meta Analysis to evaluate the efficacy of Acupuncture & Moxibustion, Clomiphene, Acupuncture & Moxibustion combined with Clomiphene for treating Polycystic Ovary Syndrome (PCOS), in order to provide evidence-based medical evidence for whether to recommend Acupuncture & Moxibustion or Combine western medicine to treat PCOS. Methods: Eight databases were searched by computer. The included research period is from the establishment of the database to May 2023, which concerned with randomized controlled trials involving Acupuncture & Moxibustion, Clomiphene, Acupuncture & Moxibustion combined with Clomiphene on ovulation induction and pregnancy outcome in patients with PCOS. using Stata17.0 software for a mesh meta-analysis. Results: Six randomized controlled trials were included, covering 1410 PCOS patients. Three interventions included Acupuncture & Moxibustion, Clomiphene, Acupuncture & Moxibustion combined with Clomiphene. Mesh Meta Analysis showed that in terms of improving ovulation rate, there was no statistical difference between Acupuncture & Moxibustion (A), Clomiphene (B), Clomiphene combined with Acupuncture & Moxibustion (C) (P>0.05). In terms of pregnancy outcome, the difference between the three intervention methods was statistically significant (P<0.05). Conclusion: Acupuncture & Moxibustion is effective in improving the ovulation promoting effect and pregnancy outcome of PCOS patients. The ovulation promoting effect of Acupuncture & Moxibustion or combined with Clomiphene is similar to that of Clomiphene alone, but Acupuncture & Moxibustion combined with Clomiphene has more advantages in improving the pregnancy rate of PCOS, and it also can reduce the adverse reactions of Clomiphene alone. Acupuncture & Moxibustion can be used as a recommended treatment for PCOS. More cases should also be included in the subgroup analysis to study the impact of Acupuncture & Moxibustion programs on clinical efficacy and further optimize the Acupuncture & Moxibustion treatment program.